Small grants for work in wetlands - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The Dutch branch of IUCN is managing the Small Grants for Wetlands programme (SWP). Grants up to US$ 75,000 ( 82,500) are available for projects in the field of conservation and sustainable use of wetlands that are executed by local NGOs in 26...